Injuries during the international floorball tournaments from 2012 to 2015 - Pasanen, Kati (BMJ Open Sport Exerc Med, 2017)
BACKGROUND: Floorball is a running indoor team sport that has growing popularity worldwide. Some prospective studies have investigated injuries in national floorball leagues, but such studies at the international level are lacking. OBJECTIVE: To investigate the incidence and characteristics of injuries during 12 International Floorball Federation (IFF) events. METHODS: All top-level IFF events from 2012 to 2015 were included in the study. The IFF events were divided into the following groups: Men’s World Floorball Championships (2012 and 2014), Women’s World Floorball Championships (2013 and 2015), Men’s Champions Cup (2012, 2013, 2014 and 2015) and Women’s Champions Cup (2012, 2013, 2014 and 2015). The team medical personnel prospectively recorded the injuries that occurred in games and practices. The time of exposure was calculated for entire teams based on the IFF statistics. RESULTS: Sixty-eight injuries were registered among 67 players. Sixty-five of the injuries occurred in games, resulting in an injury incidence of 21.24 per 1000 game hours (95% CI 16.13 to 26.35). There was no significant difference in the incidence of game injuries between females and males (incidence rate ratio 0.68, 95% CI 0.41 to 1.11). The ankle was the most common site of injury (24%), followed by the head (18%) and the knee (18%). Almost half of the injuries (46%) involved joints or ligaments. CONCLUSIONS: Risk of injury during IFF tournaments was lower than in many other team sports at the highest level of play. Preventive actions should focus on acute ankle and knee injuries as well as head and face injuries.